Tregs strip dendritic cells of CD70 to regulate Th1 differentiation - Wojciech, Lukasz (EMBO J, 2015)
When the immune system encounters an antigen, the response can result in the mobilization of effector cells or in tolerance. The outcome is largely dependent on immunosuppressive CD4 T cells that express the transcription factor Foxp3 (Tregs). Yet, how Tregs control different immune effector cells remains elusive. In this issue of The EMBO Journal, Dhainaut et al report on a novel mechanism used by Tregs to prevent differentiation of naïve CD4 T cells to proinflammatory Th1CD4 (Th1) effectors.